THE INFLUENCE OF ZAKAT LITERACY AND TRUST ON DECISIONS AND AWARENESS OF PAYING ZAKAT THROUGH AMIL ZAKAT INSTITUTIONS USING THE SEM-PLS METHOD - Muhammad Zuhri; Muhammad Sholahuddin; Moechammad Nasir (istinbath, 2023)
This research aims to determine the influence of Zakat literacy and trust in its influence on decisions and awareness in paying zakat through zakat amil institutions. The type of research is quantitative. The data collection uses survey methods, and data analysis is based on primary data obtained from the questionnaires distributed regarding the influence of Zakat literacy and trust on people's decisions in paying zakat through zakat amil institutions mediated by awareness and techniques. The sampling uses purposive sampling. The sample in this study consisted of 141 district residents of Sukoharjo who have made or are currently paying zakat through amil zakat institutions and must be at least 25 years old. The data analysis technique uses SEM PLS analysis and is analyzed using SmartPLS software, and descriptive analysis is carried out on the test result data. The results of hypothesis testing show that zakat literacy significantly affects decisions with a p-value of 0.034, trust significantly affects decisions with a p-value of 0.011, and awareness significantly affects decisions with a p-value of 0.035. Then, zakat literacy obtained a p-value of 0.000, and a p-value of trust obtained 0.000, where these two variables significantly influence awareness. Zakat literacy and trust do not significantly influence the decision to pay zakat through awareness, with a p-value for zakat literacy of 0.064 and 0.080 for trust.